DOES PUKHTUNWALI IMPEDE WOMEN POLITICS? A QUALITATIVE ANALYSIS OF DISTRICT, KOHAT-PAKISTAN - Mr Tariq Aziz; Dr Shahid Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
Women’s political participation remains a significant challenge in many underdeveloped societies. In Pakistan, despite ranking 93rd out of 153 countries, women have not achieved a prominent position in politics, despite the reserved quota seats system introduced during the Gen. Musharraf regime. This study aims to identify the barriers that restrict women’s involvement in the political arena. A qualitative approach was employed for an in-depth analysis, using open-ended interviews with twenty-five participants, including ten female party workers, ten candidates, and five female political activists, all selected through purposive sampling. The study found that Pakhtun customary practices such as the Purdah system, male dominance, perceptions of politics, participation in political campaigns, and women’s subordinate status are key obstacles to women’s political engagement.